Parametric evaluation of methotrimeprazine-midazolam-ketamine and methotrimeprazine-midazolam-ketamine-xylazine combination in dogs - Santos,Gustavo José Von Glehn dos (2006)
PURPOSE: To evaluate the parameters of dogs anesthetized by different dissociative drugs protocols through continuous intravenous infusion. METHODS: Thirty healthy dogs of both sexes were assigned randomly to three groups (G1, G2, and G3). G1 was administered with methotrimeprazine as a pre-anesthetic medication, intravenously midazolam-ketamine as bolus for induction and midazolam-ketamine by continuous intravenous infusion for a 60 minute-period of maintenance. G2: the same as for G1. plus an increase in the midazolam dose during maintenance. G3: the same treatment as for G2, plus the addition of xylazine during maintenance. Immediately after induction the anesthetic maintenance started, and measures were taken 15 minutes after pre-medication, at 10 minutes intervals, during maintenance (M0 to M7). RESULTS: Bradycardia, atrioventricular blockage, bradypnea and hypoxemia were shown in G3. G1 and G2 showed a slight hypotension only. CONCLUSION: There were some advantages by using the continuous intravenous via: no parameters oscillation and reduction in the anesthetic recovery period. The increase in midazolam dose brought about little parametric variations which were greater when xylazine was used, with a consequent hypoxemia, bradyarrhytmia, and decrease in respiratory frequency and minute volume.